2004
DOI: 10.1267/ahc.37.347
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing the Signal Transduction Pathways in Living Cells with GFP-Based FRET Probes

Abstract: Visualizing how signals are transmitted within a living cell has long been a goal of molecular biologists, which has now been realized by probes based on the principle of fluorescence resonance energy transfer (FRET). Variants of green fluorescent protein (GFP) enabled the preparation of genetically-encoded FRET probes, and their application has been expanded for use in many areas of biology. The GFP-based FRET probes can be classified as belonging to one of two types, intermolecular and intramolecular FRET pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Data obtained with RaichuRhoA fused to the carboxy-terminus of RhoA was available as supplementary data (Supplementary Figure 1 and Supplementary Video SupFig1HeLa.mov). The detailed comparison of the probes has been described elsewhere (Kurokawa et al, 2004b).…”
Section: Rhoa Is Activated At the Leading Edge Of Migrating Cellsmentioning
confidence: 99%
“…Data obtained with RaichuRhoA fused to the carboxy-terminus of RhoA was available as supplementary data (Supplementary Figure 1 and Supplementary Video SupFig1HeLa.mov). The detailed comparison of the probes has been described elsewhere (Kurokawa et al, 2004b).…”
Section: Rhoa Is Activated At the Leading Edge Of Migrating Cellsmentioning
confidence: 99%
“…Thus, we developed specific anti-R-Ras sera and a probe for R-Ras activity based on the principle of fluorescence resonance energy transfer (FRET), a technique that has been shown to be extremely useful for the spatiotemporal analysis of small GTPases (Kurokawa et al, 2004b). Using these tools, we found that endogenous R-Ras is enriched and activated at endosomes and that these R-Ras proteins promote exocytosis by activating RalA.…”
Section: Introductionmentioning
confidence: 99%
“…In general, green fluorescent protein (GFP)-based FRET sensors are classified into two types: bimolecular and unimolecular sensors (Miyawaki, 2003;Kurokawa et al, 2004). For bimolecular sensors, donor (CFP) and acceptor (YFP) are fused to protein A (e.g., the sensor domain) and protein B (e.g., the detector domain), respectively (Fig.…”
Section: Advantages Of Unimolecular Fret Sensorsmentioning
confidence: 99%
“…This is because with a unimolecular sensor protein A and protein B are placed in close proximity, and thus, protein B can easily find protein A. This will increase the percentage of real FRET signals versus undesired signals arising from donor emission bleedthrough and direct acceptor excitation (Hailey et al, 2002;Kurokawa et al, 2004). Furthermore, perturbation of endogenous signaling is reduced when using a unimolecular sensor instead of a bimolecular sensor (Miyawaki, 2003).…”
Section: Wwwintechopencommentioning
confidence: 99%